Suscetibilidade à compactação de um latossolo vermelho amarelo em função da cobertura vegetal em dois sistema de cultivo - Nascimento, Emmila Priscila Pinto do (Universidade Federal Rural do Semi-Árido, 2019)
One of the main impacts caused by agricultural mechanization is the soil compaction caused by the intense traffic of machines and implements. Another fundamental aspect in this process is the lack of soil conditions control, such as moisture and organic matter content, which may contribute to the intensification of compaction. This phenomenon is a result of the soil-machine interaction, in which the application of loads promotes changes in soil structure, influencing its physical and mechanical properties, among them, increase of soil density and resistance to root penetration, decrease of total porosity, water retention and aeration of the soil, thus determining root development and plant productivity. The objective of this study was to evaluate the effect of the bean and corn cover under minimum tillage and no-tillage systems, respectively, on soil compaction, based on mechanical parameters of non-deformed soil samples. For this, dry matter samples were collected for organic matter determination and non-deformed soil samples were collected in the 0-5, 5-10 and 10-20 cm layers for the compression test using the oedometry method. The structural voids index, the compression index and the soil pre-compression pressure were evaluated. The index of structural voids decreased with increasing water content and soil density. The compression index tends to decrease with increasing soil density or water content, revealing that the 0-5 cm layer that received the corn cover was more susceptible to compaction. The pre-compression pressure increases with increasing soil density and this effect was best observed in the 10-20 cm layer. The results showed that the soil with the bean cover and minimum growing system presented good load bearing capacity, being considered more resistant to compaction.
Monografia
Keywords: Densidade do solo; Teor de matéria orgânica; Índice de vazios; Índice de compressão; Pressão de pré-compressão; Soil density; Organic material index; Voids index; Compression index; Precompression pressure; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA